NEOTECTONICS AND MORPHOSTRUCTURAL FEATURES OF THE RELIEF OF THE RIGHT BANK OF THE MIDDLE DNIEPER REGION - Ivanik, O.; Tustanovska, L.; Hadiatska К. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of a complex structural-morphometric analysis, methods of remote sensing of the Earth and spatial modeling, the evolution of different-scale morphostructures of the right bank of the Middle Dnieper region is analyzed. Based on the created structural-morphometric models, the features of tectogenesis and morphogenesis during the Neogene-Quaternary time were revealed. The regional and local structures are characterized and the amplitudes of the latest and modern crustal movements within them are determined. The complex relationship between endogenous and exogenous relief formation has been confirmed, and the role of glacial influence on relief formation has been characterized. The nature of the relationship between structural-tectonic processes and the development of dangerous geological processes has been determined. Geological and geomorphological field studies revealed the characteristic structural and tectonic features of block structures and their influence on individual factors of geomorphogenesis. Tectonic-geomorphological modeling, taking into account morphostructural analysis, illustrated the formation of relief of various types under conditions of variable rhythms of endogenous and exogenous processes.